Evaluation of black bear (Ursus americanus) diet and consequences in its conservation in Sierra de Picachos, Nuevo León, Mexico - Luis Antonio Juárez Casillas; Cora Varas (Revista Mexicana de Biodiversidad)
Black bears (Ursus americanus) are considered endangered in Mexico. In northern Mexico, bears are considered responsible for preying on livestock, damaging private property, and crops; therefore they are killed to protect locals’ livelihoods. There is a need to understand bears’ ecological requirements in order to create conservation plans that include human-bear conflict resolution and that reduce the hunting of this endangered species. We studied the diet of black bears in the Sierra de Picachos located in the Northeast portion of the State of Nuevo León, Mexico. Our objective was to determine the diet of black bears during 3 consecutive seasons (i.e., dry, rainy, and post-rainy), and to determine the presence and frequency of livestock and crops remains in bear scats. We collected 169 scats from December 2004 to November 2005, and estimated diet composition using percentage of occurrence and volume of each food item. Plants were the most common item (73.4%), animals (16.8%), and undetermined wood fragments (9.3%). There was no statistically significant difference among seasons. Our analysis also failed to find cattle residues in any of the scats; therefore, black bears in the study site either do not or rarely feed upon livestock. We recommend that management plans include informing local people on bear behavior. Also, specific actions to avoid bear proximity should be implemented along with government actions aimed at improving bear habitat that minimize bear-human conflict in the area.